Politically motivated overseas mergers and acquisitions and stock market reactions: evidence from Chinese central state-owned business groups - Wang, Zhenning (2017)
Modern corporate governance is most characterized by management, board of directors, shareholders’ meeting, and supervision committee board. However, by investigating functions of the Party Committee, a dominant corporate governance power over modern corporate governance in Chinese central state-owned business groups (CSOBGs) , this thesis explains how Chinese CSOBGs are governed and intervened by Chinese central government and CPC at micro-level, and to what extent and under what situations political events and cadre bureaucratic system intensify the misalignment of interests between agents and principals, and how such corporate governance structure affects SOEs’ investment decisions and investment efficiency. I find that the Party Committee embeds Chinese CSOBGs’ leading executives in Chinese cadre bureaucratic system. Executives’ intention to advancement within the cadre bureaucratic system motivates the political-driven out-bound mergers and acquisitions by Chinese CSOBGs especially during critical political periods around NCCPC . I document a strong positive correlation between the promotion of leading executives of Chinese CSOBGs and the incidence of out-bound mergers and acquisitions during their tenure, and a significant negative 1-year post-acquisition performance. Furthermore, such corporate governance practice exacerbates the misalignment of the interests between non-listed Chinese CSOBGs and their listed subsidiaries, resulting in high leveraged parent tunneling from their listed subsidiaries. I report a statistically significant negative cumulative abnormal return of CSOBGs’ subsidiaries responding to these politically motivated transactions. The negative cumulative abnormal return of listed group affiliates is elucidated by critical political period, subsidiaries’ separation of ownership and control, liquidity, and parent’s leverage. I present that when CSOBGs first declare their proposals of their out-bound mergers and acquisitions, market only responds positively to their subsidiaries that are enjoying greater separation. However, the critical political periods, sensitive investment timing related to executives’ political promotion, wipes the positive influence out. With the worry of group’s tunneling, for subsidiaries with strong liquidity but a highly leveraged parent, the short-term event-driven stock performance is significantly negative. Last, consistent with previous literature, this study provides the evidence that during hot political periods, SOEs and politicians suppress negative information and disclose after the hot political periods. A significant relation between the count of news articles 3 months ahead the announcement and the short-term stock market return of out-bound mergers and acquisitions by CSOBGs is reported. Further more, stock market reactions to these news articles diverse to different political periods. I find the stock return within the event windows is negatively correlated to the news’ sentiment during the hot political periods. It indicates that the market discounts the news’ sentiment even takes them in the opposite way during the hot political periods.